Strengthening a Culture to Address Bullying and Incivility in the Care Environment. (October 2021) - Meier, Adam; Evans, Rick; Erickson, Jeanette Ives
Abstract : The safety of our patients and our workforce is paramount to elevating the health and wellness of the global communities we serve. The health and well-being of our frontline staff directly influences the environment of care, and it is our job as healthcare leaders to address workplace bullying, incivility, and lateral and horizontal violence. From patient to provider violence, to peer-peer bullying, these acts of incivility erode at the core of the care environment and impact an organization's culture of safety, influence nursing engagement scores, negatively impact patient outcomes, and decrease overall retention. Magnet ® organizations help to elevate the practice of nursing and ensure world-class interprofessional care. Therefore, the Commission on Magnet has included new language in the 2023 Magnet Application Manual in the Organizational Overview (OO7), which directly addresses the organization's structure and processes aimed at addressing workplace violence, bullying, and incivility.